Poria cocos polysaccharide—functionalized graphene oxide nanosheet induces efficient cancer immunotherapy in mice - Yang, Jinning; Dong, Xiaoxiao; Li, Boye; Chen, Tian; Yu, Boyang; Wang, Xiaoli; Dou, Xiangnan; Peng, Bo; Hu, Qin (Frontiers in Bioengineering and Biotechnology, 2023)
Tumor vaccines to induce robust humoral and cellular immune responses have attracted tremendous interests in cancer immunotherapy. Despite the enormous potential of tumor vaccine as an effective approach for cancer treatment and prevention, a major challenge in achieving a sustained antitumor immunity is inefficient antigen delivery to secondary lymphoid organs, even with adjuvant aiding. Herein, we present the antigen/adjuvant integrated nanocomplexes nsGO/PCP/OVA by employing graphene oxide nanosheet (nsGO) as antigen nanocarriers loaded with model antigen ovalbumin (OVA) protein and adjuvant - Poria cocos polysaccharides (PCP) which, when conjugated to antigens, elicits robust humoral and cellular immunity for tumor immunotherapy. With them, we evaluated their efficacy in activating antigen-specific humoral and cellular immune responses and consequent tumor prevention and rejection in vivo. The optimal formed nsGO/PCP/OVA were around 120-150 nm with uniform size distribution. Nanoparticles could be effectively engulfed by dendritic cells (DCs) through receptor-mediated endocytosis and promote the maturation of DCs as well as improve the uptake efficiency in vitro. OVA and PCP in the formed nanoparticles induced significant enhancement of antigen-specific Th1 and Th2 responses in vivo. In addition, vaccination with nsGO/PCP/OVA could not only exhibit significant suppression of tumor growth in prophylactic treatments, but also achieve a therapeutic effect to inhibit growth of already-established tumors, and generate strong humoral and cellular immunity. Therefore, this potent nanovaccine platform with nanocarrier nsGO loaded with PCP as adjuvant provided a promising strategy in boosting anti-tumor immunity for cancer immunotherapy.